IDENTIFICATION OF THE IMPACT OF THE SIMULATION LEARNING MODEL IN IMPROVING LEARNING ACTIVITIES AND ACHIEVEMENTS IN STRATEGY AND LEARNING PLANNING COURSES (International Journal of Education and Literature, 2022)
This study aims to improve the activeness and learning achievement of students by applying simulation methods in Strategy and Planning of Studying courses. This research is a class action research. The research setting was regular semester VI students, totaling 50 students who took Strategy and Planning of Studying courses. The research design involves the lecturer as the main researcher and at the same time the perpetrators of the action, the observer lecturer and students as the subject of the students. The way the research is carried out through: 1. planning, 2. implementation of class actions, 3. monitoring and evaluation, 4. analysis and reflection, 5. summarizing results. Data collection uses observation, interviews, documentation and questionnaires: Test the validity of the data using triangulation of methods and sources.Research this action by applying simulation methods in Strategy and Planning of Studying courses. The results of this action research are 1) The application of simulation learning methods can increase student activities. An increase in learning activities from cycle I to cycle II, and from cycle II to cycle III. 2) Application of simulation learning methods can optimize student learning achievement. Student learning achievement has increased from learning achievement cycle I to cycle II, and from cycle II to cycle III.